Shedding New Light on the Evaluation of Accented Speakers: Basic Mechanisms Behind Nonnative Listeners' Evaluations of Nonnative Accented Job Candidates. (January 2019) - Roessel, Janin; Schoel, Christiane; Zimmermann, Renate; Stahlberg, Dagmar
The present research unites two emergent trends in the area of language attitudes: (a) research on perceptions of nonnative speakers by nonnative listeners and (b) the search for general, basic mechanisms underlying the evaluation of nonnative accented speakers. In three experiments featuring an employment situation, German participants listened to a presentation given in English by a German speaker with a strong versus native-like accent (in Studies 1–3) versus a native speaker of English (in Study 1). They evaluated candidates with a strong accent worse than candidates with a native(-like) pronunciation—even to the degree that the quality of arguments was of no relevance (Study 1). Study 2 introduces an effective intervention to reduce these discriminatory tendencies. Across studies, affect and competence emerged as major mediators of hirability evaluations. Study 3 further revealed sequential indirect influences, which advance our understanding of previous inconsistent findings regarding disfluency and warmth perceptions.